PENGARUH PEMBERIAN POC URINE SAPI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI MERAH (Capsicum annuum L.) - Laturana, Aprilia; Yatim, Hertasning; D Hi Ahmad, Sutarmin; Maharia, Dwi (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2025)
Farmers' dependence on increasingly expensive and environmentally unfriendly inorganic fertilizers is a current problem. An alternative for farmers is the use of organic fertilizers. Organic fertilizers consist primarily or entirely of organic materials derived from plants and/or animals that have undergone a chemical or engineering process. They can be in solid or liquid form and are used to supply organic matter to improve the physical, chemical, and biological properties of the soil. Organic fertilizers can be derived from animal manure such as chicken, goat, horse, and cow. This study aims to determine the effect of cow urine on the growth and yield of red chili plants (Capsicum Annuum L.) and to find out the best concentration of cow urine on the growth and yield of red chili plants (Capsicum annuum L.). This research method uses a single factor Randomized Block Design (RAK), namely P0 = Control, P1 = 100 ml / L, P2 = 200 ml / L, P3 = 300 ml / L. The results of the study showed that the administration of cow urine in the P3 = 300 ml / L treatment gave the highest results on the growth of red chili plants. In addition, this study also showed that the treatment of administering cow urine POC had no effect on the production of red chili plants.